PENERAPAN MODEL PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Azizah; Melvi Lesmana Alim; Moh. Fauziddin; Lusi Marleni; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low critical thinking ability in the learning of science class V UPT SDN 003. Bangkinang. One solution to overcome this problem is by applying the Problem Based Instruction (PBI) learning model. The purpose of this study is to describe the improvement of critical thinking ability in science learning by applying the Problem Based Instruction (PBI) model of class V students of UPT SDN 003 Bangkinang. The research method is classroom action research (CAR) which is carried out in two cycles. Each cycles consists of two meetings and four stages, namely, planning, implementation, observation, and reflection. The subjects of this study were 22 class V students. Data and collection techniques were observation and documentation. Based on the results of data analysis, it can be seen that the increase in the results of students’ critical thinking abilities after the action, the average completeness of the results of critical thinking abilities was only 68 whith classical completeness of 40,90%, then in cycle I meeting I increased to 72 whith classical completeness of 50%, then in cycle I meeting II increased to 75 whith classical clompeteness of 59,10%. Furthermore, cycle II meeting I increased to 80 with classical clompeteness of 72,72% and cycle II meeting II increased to 83 with classical clompeteness 86,36%. Therefore, it can be concluded that the applicatition of the Problem Based Instruction (PBI) model can improve crotical thinking skills in science learning for fifth grade students of UPT SDN 003 Bangkinang.